Climate Change Education as an Adaptative Strategy for Dairy Farmers: A Sociocultural Perspective - Silvia Lizette Ramos de Robles; Xochitl Barbosa Carmona; Alejandro José Gallard Martínez; Juan Alberto Gran Castro (ECNU Review of Education)
Purpose This study aims to develop a transdisciplinary informal curriculum for climate change education (CCE) to increase the adaptive capacity of the small-farm milk-producing sector in Encarnación de Díaz, Jalisco, México. Design/Approach/Methods A sustainable rural livelihood framework assessing six types of capital (animal, financial, human, natural, physical, and sociocultural) in a sequential exploratory method design was used to determine the adaptive capacity of 61 milk producers to climate change. Several interrelated aspects of capital are associated with milk producers’ vulnerability to climate change. Findings Dairy farmers’ knowledge is based on traditional, historical, and cultural ways of interacting with their environment. Respecting this knowledge allowed us to use their experiential knowledge to co-jointly develop a CCE model to decrease the vulnerability of each of the six identified types of capital, with financial, human, and sociocultural capital being the most vulnerable. Originality/Value Using local knowledge to cultivate adaptive actions for climate change and reducing the vulnerability of affected communities is essential when developing an informal CCE curriculum.